Experimental evaluation of the robustness of the growth–stress tolerance trade‐off within the perennial grass Dactylis glomerata. (30th April 2018) - Bristiel, Pauline; Gillespie, Lauren; Østrem, Liv; Balachowski, Jennifer; Violle, Cyrille; Volaire, Florence
Abstract : Plain Language Summary Abstract: A core tenet of functional ecology is that the vast phenotypic diversity observed in the plant kingdom could be partly generated by a trade‐off between the ability of plants to grow quickly and acquire resources in rich environments vs. the ability to conserve resources and avoid mortality under stress. However, experimental demonstrations remain scarce and potentially blurred by phylogenetic constraints in cross‐species analyses. Here, we experimentally decoupled growth potential and stress survival by applying an off‐season stress on contrasting populations of the perennial grass Dactylis glomerata exhibiting a range of seasonal dormancy. Seventeen populations of D. glomerata, originating from a latitudinal gradient from Norway to Morocco, were subjected to three types of dehydration stress: winter frost in Norway, and summer drought and early spring (off‐season) drought stress in the south of France. Growth rate and two leaf traits (leaf width and leaf dry matter content) suspected to be involved in the adaptation to dehydration stress were monitored under optimal conditions. We quantified plant dehydration survival as the amount of plant recovery after a severe stress. Nordic populations were found to be winter‐dormant. Winter‐ and summer‐dormant populations better survived frost and summer drought, respectively. However, no trade‐off between growth potential and dehydration survival was detected in non‐dormant plants in early spring when dehydration occurred unseasonably for all populations. Furthermore, Mediterranean populations better survived an early spring drought. Our results highlight the importance of assessing plant growth potential as a response to seasonal environmental cues. They suggest that growth potential and stress survival trade off when plants exhibit seasonal dormancy but can be functionally independent at other seasons. Consequently, the growth–stress survival relationship could be better described as a dynamic linkage rather than a constant and general trade‐off. Moreover, leaf trait values, such as thinner and more lignified leaves reflecting drought adaptation, may have contributed to the improved drought‐stress survival without resulting in a cost to growth. Further exploration of the growth–stress survival relationship should permit deciphering the suite of plant traits and trait covariations involved in plants' responses to increasing stress. A plain language summary is available for this article.